How different are shyness and assertiveness in Croatian males and females? - Zarevski, Predrag (Array, 1999)
The question was whether or not the questionnaires used to assess shyness and assertiveness measure the same construct for men as well as for women. The aim of the investigation was to establish the degree of congruence between the latent dimensions of shyness and assertiveness in Croatian male and female subsamples. Subjects (545 females and 517 males) were randomly selected from a population of individuals with a college or university degree, aged 18-40. Male and female versions of Shyness scale (Zarevski, 1997) and Assertiveness scale (Vukosav & Zarevski, 1997) were administered. Factor analysis revealed that the first principal component in both sub-samples is a general measure of shyness/non-assertiveness. On the positive pole of the second component situations demanding a subject's assertive reactions were positioned, while on the negative pole items related to shyness were positioned. Following the rotation, clear factors of shyness and assertiveness were obtained. Since only ten percent of the variance was shared between the shyness and assertiveness factors, it was justifiable to measure each of the constructs separately. In the Croatian population, generally speaking, there is no either male or female shyness, nor assertiveness, however, there are some situations where reactions and perceptions are related to gender.